Histopathology of Heart Rats (Rattus norvegicus) Due to the Use of Cooking Oil - Siti Aisyah; Ummu Balqis; Eko Karunia Friyan (Universitas Syiah Kuala, 2014)
This research aims to study the histopathological picture of rats (Rattus norvegicus) heart as a result of the provision of waste cooking oil3x, 6x, and 9x frying. This study used 20 male white rats (Rattus norvegicus) weighing of ± 300 g. Rats were grouped into 4 treatment groups,adapted for one week, feed and drink ad libitum. The second week to eight week rats were given orally cooking oil every day with a dose of 1 ml. A group of rats was given cooking oil (negative control). Group B, C, and D were given cooking oil 3x, 6x, and 9x frying. Mi ce were euthanizedafter 60 days, then necropsied to collect the heart. Heart was then put into Neutral Buffered Formalin (NBF) for fixation, then follow withhistopathology preparation. Parameters measured were hyperemia, hemorrhage, degeneration, necrosis of the heart. Results were analyzeddescriptively with the scoring system. Test results are grouped into three categories, namely, mild (+), moderate (++), and weight (+++). Thehystopathological results of the heart found were an increasing number of hyperemia, hemorrhage, degeneration, necrosis as a result of thefrequency of frying.____________________________________________________________________________________________________________________Key words: heart, cooking oil, rats